The reliability of wearable commercial sensors for outdoor assessment of running biomechanics: the effect of surface and running speed - Kozinc, Ž.; Smajla, D.; Sarabon, N. (Sports Biomechanics, 2022)
The aim of this study was to investigate the reliability of running biomechanics assessment with a wearable commercial sensor (RunScribeTM). Participants performed multiple 200-m runs over sand, grass and asphalt ground at the estimated 5-km tempo, with an additional trial with 21-km tempo at the asphalt. Intra-session reliability was excellent for all variables at 5-km pace (intra-class coefficient correlation (ICC) asphalt: 0.90-0.99; macadam: 0.94-1.00; grass: 0.92-1.00), except for shock (good; ICC = 0.83), and contact time and total power output (moderate; ICC = 0.68-0.71). Coefficient of variation (CV) were mostly acceptable in all conditions, except for horizontal ground reaction force (GRF) rate in asphalt 5-km pace trial (CV = 24.5 %), power (CV = 14.3 %) and foot strike type (CV = 30.9 %) in 21-km pace trial, and horizontal GRF rate grass trial (CV = 15.7 %). Inter-session reliability was high or excellent for the majority of the outcomes (ICC=0.85). Total power output (ICC = 0.56-0.65) and shock (ICC = 0.67-0.75) showed only moderate reliability across all conditions. Power (CV = 12.5-13.8 %), foot strike type (CV = 14.9-29.4 %) and horizontal ground reaction force rate (CV = 12.4-36.4 %) showed unacceptable CV.